Karakterisasi Aliran Uap-Kondensat pada Saluran Mendatar Berdasarkan Pengukuran Temperatur - Sukamta, Sukamta; Indarto, Indarto; Purnomo, Purnomo; Rokhmat, Tri Agung (Jurnal Semesta Teknika, 2014)
The objective of the current investigation is to find out temperature distribution regimes in a horizontal pipe when condensation process is happened.Â  The research was conducted at Pusat Studi Ilmu Teknik Universitas Gadjah Mada. The experiment apparatus consists of an inner annulus pipe made from copper (din = 17.2 mm, do = 19 mm) with the length of 1.8 m. The outer annulus pipe is a galvanized iron pipe (din = 108.3 mm, do = 114.3 mm) with the length of 1.6 m. Thermocouples type K 36 TT OMEGA with chromel (+) and alumel (-) materials were used as temperature sensors, to detect the spread of temperature in radial or axial direction along the pipe. The measurement ranged from -50 to 260 oC, with an accuracy of 0.01 Â°C. A data logger of RX 40 serial (OMRON, 20 Channels) was used to read and record temperature data with the sampling rate of 5 Hz. In the experiment, the water (H2O)was heated using a boiler to generate steam which was then flowed and condensed inside the annulus pipe to form a steam-condensate two-phase flow in horizontal pipe. On the other hand, the water was used as a coolant in the outer of annulus pipe. The results indicated that the temperature distribution regimes are influenced by axial posisition.The farther distances from the inlet the lower the temperatures being recorded which indicate the increase of film condensate thickness. Such phenomena can affect slugging in the location.